Pengembangan Multimedia Interaktif Pada Pembelajaran Pendidikan Pancasila di Sekolah Dasar - Ainila Pradi Sespen; Yalvema Miaz (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study is motivated by the limited variety of interactive learning media in Pancasila Education at the elementary school level, which results in low student engagement. The use of interactive multimedia based on the Book Creator application is expected to improve students’ motivation, understanding, and participation. This research employs a Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation, involving fifth-grade students from SD Negeri Percobaan Padang, SDN 24 Ujung Gurun, and SDN 05 Padang Pasir. The research instruments consisted of expert validation sheets, practicality questionnaires, and pre-test and post-test items to measure effectiveness. The data analysis techniques included descriptive quantitative analysis to calculate the percentages of validity, practicality, and effectiveness, as well as N-Gain calculations to determine the improvement in learning outcomes. The results showed that the media obtained high validation scores from material experts (90%), media experts (83%), and language experts (97%), categorized as very valid. In the practicality test, teachers gave a score of 96% and students 92%, both categorized as very practical, while the effectiveness test yielded a score of 82%, categorized as effective. Continuous evaluation was conducted to ensure that the media remained aligned with the curriculum, students’ needs, and technological developments. Thus, the Book Creator interactive multimedia is declared valid, practical, and effective, and can serve as an engaging and meaningful alternative learning medium in Pancasila Education at the elementary school level.